Airport Privatization in India: Case of Indira Gandhi International Airport, Delhi - Mohan Phuyal (An Overview on Business, Management and Economics Research Vol. 3, 2023)
This research focuses on the airport privatization in India, with a specific case study of the privatization of the Indira Gandhi International Airport (IGIA) in Delhi. Public-Private Partnerships, or PPPs, have been used since the 1990s in India to include the private sector in airport development, modernisation, and operation. Successful PPP implementation can be seen at large international airports like IGIA, Indira Gandhi in Delhi, CSIA Chhatrapati Shivaji Maharaj International Airport in Mumbai, Cochin in Kochi, etc. This study examines the motivations, processes, outcomes, and associated with the privatization of IGIA. The Indian airports are perceived as being more business-oriented than government-owned. Privatization measures were consequently put into practice. By encouraging private investments in the construction of airport infrastructure, India’s airport shortage has been fueled. With the opening of Cochin International Airport in 1999, the GoI took significant initiatives with the assistance of the business sector. It has promoted PPP strategies in brownfield and new airport developments since 2006. There were six airports covered under PPP model agreements altogether. One of the notable PPP initiatives in the Indian airport industry was the IGIA. An active PPP project is IGIA. The DIAL PPP framework has been effective in encouraging private sector investments in airport infrastructure and in enhancing the quality of services provided by the airports. It’s important to note that determining whether the IGIA PPP was successful or unsuccessful will take time.